2011
DOI: 10.1039/c0cc02245d
|View full text |Cite
|
Sign up to set email alerts
|

Double addition of H2to transition metal–borane complexes: a ‘hydride shuttle’ process between boron and transition metal centres

Abstract: The addition of H(2) across a transition metal-borane bond is reported for the first time providing a mechanism for recharging borane functional groups to borohydride.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 22 publications
2
82
0
2
Order By: Relevance
“…In a seminal discovery, Peters and co-workers reported cooperative activation of H 2 across an inverse dative Ni→B σ-bond to generate a H−Ni(µ−H)B species that catalyzes olefin hydrogenation [39,67]. The B(III) support was proposed to play a direct role in H−H cleavage in this and related systems [67,69,70]. We aimed to vary the Lewis acid support so as to systematically examine its role in promoting H 2 binding, cleavage, and hydrogenation catalysis in cooperation with an active transition metal.…”
Section: Nickel-group 13 Hydrogenation Catalystsmentioning
confidence: 97%
“…In a seminal discovery, Peters and co-workers reported cooperative activation of H 2 across an inverse dative Ni→B σ-bond to generate a H−Ni(µ−H)B species that catalyzes olefin hydrogenation [39,67]. The B(III) support was proposed to play a direct role in H−H cleavage in this and related systems [67,69,70]. We aimed to vary the Lewis acid support so as to systematically examine its role in promoting H 2 binding, cleavage, and hydrogenation catalysis in cooperation with an active transition metal.…”
Section: Nickel-group 13 Hydrogenation Catalystsmentioning
confidence: 97%
“…4,5 First-row metallaboratranes and related compounds that contain a retrodative M→B σ-interaction 6 are appealing as catalysts 7 because of the boron center’s ability to stabilize low valent metals. 8 Akin to frustrated Lewis pairs, 9 it has also been recently demonstrated that the metal-boron interaction can cooperatively facilitate the activation of H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…8 Akin to frustrated Lewis pairs, 9 it has also been recently demonstrated that the metal-boron interaction can cooperatively facilitate the activation of H 2 . 5,7 For instance, our lab recently reported that the diphosphine-borane nickel ( Mes DPB Ph )Ni complex undergoes reversible oxidative addition of H 2 to afford a nickel-borohydrido-hydride complex (Scheme 1). 10 This nickel system is an efficient catalyst for olefin hydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…[2,[19][20][21] Structurally authenticated complexes containing ad irect reverse-dative s-interaction between at ransition metal and ab orane were unknown prior to Hillss eminal report of the first metalloboratrane. [2,[19][20][21] However, despite the reactive nature of the M!BR 3 linkage,substrate activation reactions occurring across this bond have been limited almost exclusively to formal oxidative addition/ heterolytic bond cleavage, [4][5][6][7][8][9][10][11][12][13] with H 2 oxidative addition and hydride shuttling receiving much of the attention. [2,[19][20][21] However, despite the reactive nature of the M!BR 3 linkage,substrate activation reactions occurring across this bond have been limited almost exclusively to formal oxidative addition/ heterolytic bond cleavage, [4][5][6][7][8][9][10][11][12][13] with H 2 oxidative addition and hydride shuttling receiving much of the attention.…”
mentioning
confidence: 99%